Anteater nose sign and reverse anteater nose sign: Are they specific for calcaneonavicular coalition? - Bhoil,Rohit; Ahluwalia,Ajay; Sharma,Ritu; Das,Abhishek; Jhobta,Anupam (Journal of Musculoskeletal Surgery and Research)
The anteater nose sign has been described on imaging in the case of the calcaneonavicular coalition and is produced by a tubular elongation of the anterior calcaneal process that approaches or overlaps the navicular bone, resembling an anteater’s nose. Similarly, the reverse anteater sign refers to the posterior and lateral extension of the navicular bone, also seen in the case of the calcaneonavicular coalition. Originally described on lateral or oblique foot/ankle radiographs, this appearance is also observed in the case of magnetic resonance images (MRI) on sagittal sections. We describe a case of a talocalcaneal coalition, in which the MRI had a similar appearance, thereby confusing the imaging findings of the case, and discuss the key imaging features for the correct diagnosis. We also propose a new sign, “Opposing beak sign,” for this similar appearance in the case of a talo-calcaneal coalition, awareness of which as a distinct entity on sagittal MRI would help correct preoperative diagnosis and subsequent management.